Environmental Education - A Commitment Assumed by Elementary School Teachers - VÁSQUEZ TOMÁS, Melba Rita; BALDEÓN DE LA CRUZ, Maruja Dionisia; YANGALI VICENTE, Judith Soledad; HUAITA ACHA, Delsi Mariela; REYNOSA NAVARRO, Enaidy (Journal of Environmental Management and Tourism, 2022)
Through the Ministries of Education and the Environment, Peru has been concerned with implementing educational policies to provide students with a solid environmental education, turning teachers into trainers of environmentally responsible people. The research using a case study allowed us to know the reflections and actions developed by primary education teachers to contribute to the environmental education of their students. For this reason, interviews were conducted with teachers from public schools in the Lima-metropolitan area (Peru). As a result of the analysis of the participants' speeches, the interest in planning and implementing learning experiences related to the environmental approach was evidenced. This was done to generate reflection and participation of students in the environmental problems of their school and local environment.